Direct N2O emissions from global tea plantations and mitigation potential by climate-smart practices - Wang, J.; Smith, P.; Hergoualc'h, Kristell; Zou, J. (Elsevier, 2022)
Estimating N2O emissions from the agricultural sector and developing effective reduction strategies are essential to achieving the Paris Agreement 2 °C target. Based on 3705 observations from 435 articles, we demonstrated that the response of N2O emissions was more sensitive to N inputs on acidic soils than alkaline soils and that climatic factors influence this difference. Total global N2O emissions from tea plantations in the 2010s were estimated to be 46.5 Gg N yr–1 using an exponential model developed herein. Tea plantations are a significant contributor to N2O emissions from the agricultural sector in several countries. The intensity of yield-scale GHG emissions from tea was significantly higher than in other upland cereals. Applying climate-smart practices in Chinese tea plantations could reduce emissions equivalent to one-third of the global total. We conclude that accurate identification of N2O emission hotspots and implementation of targeted measures are essential to achieving global temperature control targets.